The year of the perfect Christmas tree : an Appalachian story - Houston, Gloria (Dial Books for Young Readers, 1988)
Ruthie and her mother wonder how they will fulfill their obligation of getting the perfect Christmas tree to the town for the holiday celebration, since Papa has left the Appalachian area to go to war.